A workforce planning and allocation model for the outbound baggage loading area at Santiago International Airport. Issue 3 (2nd July 2020) - Cavada, Juan Pablo; Cortés, Cristián E.; Rey, Pablo A.
Abstract: A methodology is presented that determines the staff requirements for a baggage handling operation at an international airport facing high demand. It consists of two sequentially solved integer linear programming models. The first model determines the handler requirement using historical demand data and incorporates the operation's spatial constraints. The second model, taking as input the results of the first model, defines each handler's shift and task assignments. This formulation can be considered as the solution of a set covering problem using feasible shift structures pre-defined by an algorithm. The proposed approach is validated in an application to a real-world case, demonstrating significant improvements over the baggage handling operator's own staff planning decisions.